1989
DOI: 10.1073/pnas.86.1.307
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte antigen Leu-19 as a molecular marker of regeneration in human skeletal muscle.

Abstract: Antigen Leu-19 (Leul9-Ag), a 200-to 220-kDa surface glycoprotein, was originally identified on a subset of human peripheral lymphocytes exhibiting non-major histocompatibility complex-restricted cytotoxicity. Here we report that monoclonal antibody Leu-19 (mAb-Leu19) labels structures in human skeletal muscle: (i) satellite cells, which form the stem cell pool of muscle fiber regeneration, both in normal and diseased muscle; (ii) myotubes and myotube projections in regions of muscle fiber repair; (iii) periodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(69 citation statements)
references
References 19 publications
2
67
0
Order By: Relevance
“…Unlike desmin and creatine kinase, it is absent from mature myocytes (Schubert et al, 1989). Our results showed that CD56 and desmin are differentially regulated by TGF-b2.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Unlike desmin and creatine kinase, it is absent from mature myocytes (Schubert et al, 1989). Our results showed that CD56 and desmin are differentially regulated by TGF-b2.…”
Section: Discussionmentioning
confidence: 56%
“…Its up-regulation is a signal of myoblast differentiation. CD56 (also named NCAM or Antigen Leu-19) is expressed constituitively in proliferating myoblasts (Illa et al, 1992;Belles-Isles et al, 1993), but is absent in mature muscle (Schubert et al, 1989). Other cells also express CD56, including certain lymphocytes and neurons, but not fibroblasts.…”
mentioning
confidence: 99%
“…Five-micrometer thick cryosections were prepared according to earlier protocols (24): fixed in ice-cold acetone at 220°C for 20 min, air-dried, and then rehydrated in PBS (pH 7.4) at room temperature. Peripheral blood mononuclear cells (PBMC) were prepared as described (25).…”
Section: Preparation Of Cells and Tissue Sectionsmentioning
confidence: 99%
“…Among those are cell adhesion molecules (Rutishauser and Jessell, 1988;Edelman, 1992), in particular the neural cell adhesion molecule (NCAM, Rutishauser and Jessell, 1988). NCAM has previously been found on activated satellite cells (myoblasts) and on myotubes during regeneration or on the entire sarcolemma of muscle fibers after denervation (Covault and Sanes, 1985;Moore and Walsh, 1986;Schubert et al, 1989). Thus, NCAM is one molecular marker of regenerating and denervated muscle fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, NCAM is one molecular marker of regenerating and denervated muscle fibers. In normal adult muscle, NCAM is expressed at the neuromuscular junction (Covault and Sanes, 1986) and has been occasionally observed in satellite cells (Covault and Sanes, 1986;Cashman et al, 1987;Schubert et al, 1989).…”
Section: Introductionmentioning
confidence: 99%